Update on the CFIB, the French Speaking Patent Information User Group. (June 2015) - Baudour, Frederic; Bodart, Philippe; Bourbon, Emmanuelle; Bourgeois, Muriel; Bourge, Pierre-Olivier; Boyer-Joubert, Cecile; Hutsebaut, Samuel; Windels, Fabienne
Abstract: Over the last few years, the French Patent Information User Group (CFIB) has re-organized itself and considerably developed its activities. This article is an overview of the association's current activities.